Microbiome Metabolite Mimics Accelerate Drug Discovery. Issue 5 (May 2020) - Nuzzo, Andrea; Brown, James R.
Abstract : A recent study by Dvořák et al. supports metabolite mimicry as a drug development strategy. A potent agonist of the human pregnane X receptor (hPXR) was designed from two ligands that are products of the microbial catabolism of tryptophan. Its validity was demonstrated in cellular assays and a murine colitis model expressing hPXR by a significant reduction in inflammation biomarkers.